Molecular identification of enterotoxigenic Bacteroides fragilis and the Distribution 16S rRNA gene, bft gene subtypes and gyrb gene in Iraqi patients with diarrhea - Hussein Ali Khaleefah; Ashwak Basim Jasim; Saher Gazi Omeran (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
This study includes 50 stool: 21 patients with diarrhea and 29 healthy control samples were collected from different hospitals in Baghdad city (Baghdad teaching hospital, AL-yarmok teaching hospital and Pediatric teaching Hospital at the beginning of March/2020 to the end April/2021 . DNA was extracted directly from stool specimens and conventional PCR targeting 16S rRNA gene gyrb gene used for B.fragilis detection, Bacteroides fragilis toxin (bft) gene used for detection of ETBF. The results showed that presence of 16S rRNA gene was detected in 17(32%) stool samples included 7(41.17%) of patients and 10 (58.8%) of control group . Presence of gyrb gene was detected in 9(52.9%) stool samples included 4 (44.4%)of patients and 5 (55.5%) of control group: the incidence of bft gene in 4(23.5%) stool samples included : 3 of patients and 1 control .bft2 and bft3 were found in 1 and 2 samples from 3 diarrheic patients with ETBF respectively.bft1 present in one sample in control group.